Oxidative stress response in canine in vitro liver, kidney and intestinal models with seven potential dietary ingredients. (22nd January 2016) - Choi, Kyoungju; Ortega, Maria T.; Jeffery, Brett; Riviere, Jim E.; Monteiro-Riviere, Nancy A.
Highlights: The development of canine in vitro culture systems with multiple organ-derived cells. An assessment of cellular oxidative stress and antioxidant responses by potential food ingredients in canine liver, kidney, and intestinal cells. Chemical- and organ-specific oxidative stress and antioxidant properties may implicate a mechanism of toxicity. Abstract: In vitro cell culture systems are a useful tool to rapidly assess the potential safety or toxicity of chemical constituents of food. Here, we investigated oxidative stress and organ-specific antioxidant responses by 7 potential dietary ingredients using canine in vitro culture of hepatocytes, proximal tubule cells (CPTC), bone marrow-derived mesenchymal stem cells (BMSC) and enterocyte-like cells (ELC). Cellular production of free radical species by denatonium benzoate (DB), epigallocatechin gallate (EPI), eucalyptol (EUC), green tea catechin extract (GTE) and sodium copper chlorophyllin (SCC), tetrahydroisohumulone (TRA) as well as xylitol (XYL) were continuously measured for reactive oxygen/nitrogen species (ROS/RNS) and superoxide (SO) for up to 24 h. DB and TRA showed strong prooxidant activities in hepatocytes and to a lesser degree in ELC. DB was a weak prooxidant in BMSC. In contrast DB and TRA were antioxidants in CPTC. EPI was prooxidant in hepatocytes and BMSC but showed prooxidant and antioxidant activity in CPTC. SCC in hepatocytes (12.5 mg/mL) and CPTC (0.78 mg/mL) showed strong prooxidant and antioxidant activity in a concentration-dependent manner. GTE was effective antioxidant only in ELC. EUC and XYL did not induce ROS/RNS in all 4 cell types. SO production by EPI and TRA increased in hepatocytes but decreased by SCC in hepatocytes and ELC. These results suggest that organ-specific responses to oxidative stress by these potential prooxidant compounds may implicate a mechanism of their toxicities.